Meningkatkan Hasil Belajar Siswa Dengan Menerapkan Model Pembelajaran Project Based Learning (PJBL) Pada Materi Menyusun Huruf Vokal Dan Konsonan Menjadi Kata Yang Bermakna Pada Siswa Kelas I SD YPPK Keakwa - Nofriana Delima Bouk (Concept: Journal of Social Humanities and Education, 2022)
This research aims to determine student learning outcomes on the material of arranging vowels and consonants into meaningful words using the Project Based Learning (PjBL) learning model in class I of YPPK Keakwa Elementary School. This research was carried out at YPPK Keakwa Elementary School. The method used in this research is classroom action research (PTK) which consists of several cycles until indicators of success in the action can be achieved. The research subjects were 24 class I students. The instrument used was to collect data in this research using an observation test. The test used was a description. Based on the results of the research data processing, it was found that in cycle I it showed that student learning outcomes when implementing the Project Based Learning (PjBL) learning model were obtained on average 73.33 with the highest score of 90 obtained by 1 person and the lowest score of 50 obtained by 4 people with a completion percentage of 78.38% after the teacher reflected and corrected several deficiencies so that student learning outcomes in cycle II increased to 100% with an average score of 85.0 with the highest score of 100 obtained by 2 people and the lowest score of 70 obtained by obtained by 7 people and have reached the standard of learning completeness. So it can be concluded that by implementing the Project Based Learning (PjBL) learning model the material for arranging vowels and consonants into meaningful words in Class I of YPPK Keakwa Elementary School has improved significantly so that it can be used as an alternative in learning.